The Influence of Financial Literacy on Financial Management of UMKM in Palopo City - Asriany; Muh. Yusuf Q; Samsul Bachri; Jumawan (www.amertainstitute.com, 2024)
Financial literacy refers to an individual's understanding of financial concepts and their ability to manage finances effectively. For UMKM (Micro, Small, and Medium Enterprises), financial literacy plays a critical role in ensuring sound financial management and long-term business success. This study investigates the impact of financial literacy on the financial management practices of UMKM in Palopo City. The research employs an associative approach and involves a sample of 50 UMKM in Palopo City, using primary data collected through questionnaires. The analysis utilizes simple regression to assess the relationship between financial literacy and financial management. The findings reveal that financial literacy has a positive and significant effect on the financial management of UMKM. This implies that UMKM with higher levels of financial literacy are better equipped to manage their business finances, including budgeting, investment decisions, and resource allocation. The results underscore the importance of improving financial literacy among UMKM operators to enhance their financial decision-making and business performance. These findings highlight the need for targeted financial education programs tailored to UMKM, focusing on practical financial skills and knowledge. Future research could expand the scope by exploring additional factors influencing financial management, such as access to financial services, digital literacy, and entrepreneurial experience.